Electrical characteristics of ZnxIn2S3+x single crystals - Jitari, Vasile (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2011)
The electrophysical characteristics, including the Hall effect, of the family of layered ZnxIn2S3 x (x = 1, 2, and 3) compounds were studied in a temperature range of 250–500 K ( C). They were interpreted taking into account an exponential distribution of traps near the conduction band. The main parameters of the material were determined, and the way was shown how they can be varied.